2020
DOI: 10.3390/v12121349
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Yellow Fever in Asia: History, Hypotheses, Vector Dispersal, Possibility of YF in Asia, and Other Enigmas

Abstract: Since the recent epidemics of yellow fever in Angola and Brazil as well as the importation of cases to China in 2016, there has been an increased interest in the century-old enigma, absence of yellow fever in Asia. Although this topic has been repeatedly reviewed before, the history of human intervention has never been considered a critical factor. A two-stage literature search online for this review, however, yielded a rich history indispensable for the debate over this medical enigma. As we combat the pandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 180 publications
(249 reference statements)
2
27
0
Order By: Relevance
“…This is in agreement with the current literature, which suggests that multiple societal, biological and environmental factors likely contribute to the absence of YF in Asia. 8 , 27 , 77 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with the current literature, which suggests that multiple societal, biological and environmental factors likely contribute to the absence of YF in Asia. 8 , 27 , 77 …”
Section: Discussionmentioning
confidence: 99%
“… 25 It has been suggested that YF had fewer historic opportunities for introduction into Asia, as Asian–African trade routes were primarily with East Africa, where YF incidence was lower. 26 , 27 However, as YF spread to both the Americas and Europe, it is unlikely that the opportunity for YF introduction into Asia never occurred. 25 Successful control of YF across Africa and the South America, through preventive vaccination campaigns or outbreak response vaccination, may have limited YF introduction into Asia during the 20th century.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, YF is endemic in mostly South American and Africa, with outbreaks consistently seen each year. Although not often heard about in North America and Asian countries, Yellow Fever was endemic hundreds of years ago in cities like New York, Philadelphia, Memphis, and New Orleans [19] and has the possibility to emerge in Asian countries [20,21]. Although Aedes mosquitoes are also native in parts of Asia, the absence of YF cases has long been a scientific enigma [21,22].…”
Section: Yellow Fever Virusmentioning
confidence: 99%
“…Although not often heard about in North America and Asian countries, Yellow Fever was endemic hundreds of years ago in cities like New York, Philadelphia, Memphis, and New Orleans [19] and has the possibility to emerge in Asian countries [20,21]. Although Aedes mosquitoes are also native in parts of Asia, the absence of YF cases has long been a scientific enigma [21,22]. Common theories to the lack of YF cases in Asia are: the east African mountain range provides a natural barrier for Asia [21], competition with Dengue virus limits YF transmission [23], and vector competency [20] among others.…”
Section: Yellow Fever Virusmentioning
confidence: 99%
See 1 more Smart Citation